ChemInform Abstract: Ionic‐Radius‐Driven Selection of the Main‐Group‐Metal Cage for Intermetalloid Clusters [Ln@PbxBi14‐x]q‐ and [Ln@PbyBi13‐y]q‐ (x/q = 7/4, 6/3; y/q = 4/4, 3/3). Issue 14 (April 2015) - Ababei, Rodica; Massa, Werner; Weinert, Bastian; Pollak, Patrik; Xie, Xiulan; Clerac, Rodolphe; Weigend, Florian; Dehnen, Stefanie
Abstract: Reactions of the binary Zintl anion (Pb2 Bi2 ) 2‐ with Ln(Me4 Cp)3 (Ln: La, Ce, Nd, Gd, Sm, Tb) in presence of [2.2.2]crypt in en/toluene yields ten [K([2.2.2]crypt)] + salts of Ln‐doped semimetal clusters with 13 or 14 surface atoms.